Relação entre língua materna e língua estrangeira: o "erro" em produções escritas de adolescentes estudantes da língua inglesa. - Miranda, Letícia Campos (2021)
With globalization, the distance between places have shortened, and as consequence of this process came the valorization of the plurilinguism. Based on that, teenagers are part of the target public, first because of their interest in what is happening around, and second because of their curiosity and openness to learn new languages. Some teenagers feel blocked when trying to learn a new language while others flow through it like native speakers, and we believe that this difference exists by unconscious reasons. In order to contribute to this question we have developed a research whose general objective is to investigate this “mistakes” as effects of the relation between the subject and its mother language in teenagerscomposings that are in process of acquisition of a foreign language. More specifically we had these objectives: analyze the metaphoric and metonymic operation in teenagers productions; identify the disruption, as lapses, hesitations, interruptions, the non coincidences in their productions; indicate the relation between mother and foreign language out of the previous objectives. For that, we have worked with teenagers students of an English course that, after reading tales from English language, wrote texts that were analyzed in order to identify “mistakes” – understood as effects of the relation of the subject and the mother language – present in the writing of their productions. Analyze procedures were guided by the literature that bases the research and that concerns Linguistics and Psychanalysis, as the notion of equivocality/incompleteness of the sign and the language theory and the subject in Lacan. In the analysis of the texts produced by the students that were part of the research we could highlight the places where the relation with the mother language was visible in the “mistakes”. Was indicated, however, that the interference of this relation is heterogeneous, what, therefore, made noticeable the singular condition of the student of foreign language, as unconscious subject captured by the structural operation of the language.